Joint processing of measurements in a rangefinder-doppler multistatic radar system - E. G. Borisov (Научный вестник МГТУ ГА)
The article considers the option of organizing joint processing of radar information in a multistatic rangefinder - doppler radar system. The least-squares method is used to obtain analytical expressions for oblique ranges and radial velocities of targets during joint processing of range-finding measurements of various types. The obtained expressions for inclined ranges have some similarities with the secondary processing of radar information, with the only difference being that the weighting coefficients for the evaluated parameters are updated in the case of successive measurements as data are received, and in the case of joint processing, they depend on the number of positions and the number of measurements. It is shown that the joint processing of measurements of the inclined range, the sum of the distances, the radial velocity and the rate of change of the total range allows to increase the accuracy of measuring the location of an air object and the projections of its velocity vector on the axis of a rectangular coordinate system. The physical basis for increasing the accuracy of positioning is to use redundant measurements by processing the total ranges. The considered option of processing redundant measurements in a multistatic radar system does not require time to accumulate data, and the task of increasing accuracy is solved in one measurement cycle. The potential accuracy of determining the location of an air object for different values of the standard errors of the determination of rangefinding parameters in a multistatic radar system at various distances between positions has been calculated. For an arbitrary trajectory of an air object, simulation-statistical modeling was performed, which allows to obtain the mean square errors of determining the location and velocity vector of the air object. A gain is shown in the accuracy of determining the location and velocity vector of an air object in comparison with traditional algorithms for determining coordinates in long-range multistatic radar systems.